Red blood cell exchange to avoid intubating a COVID‐19 positive patient with sickle cell disease?. Issue 4 (6th July 2020) - Allison, David; Campbell‐Lee, Sally; Crane, Jason; Vidanovic, Vladimir; Webb, Shaun; Fraidenburg, Dustin; Hussain, Faiz
Abstract: As the COVID‐19 pandemic continues to claim lives across the globe, insufficient data exists regarding the optimal treatment. It is well known that patients 55 years of age or older and patients with certain chronic diseases are at higher risk of severe illness, including acute respiratory distress syndrome and death. A potentially fatal pulmonary complication of sickle cell disease, acute chest syndrome, can be precipitated by acute infections, including respiratory viruses. We report the case of a patient with sickle cell disease (HbSC) who developed COVID‐19 pneumonia and acute chest syndrome who was treated with emergent red blood cell exchange in order to avoid endotracheal intubation.